Intrusion of deciduous and permanent teeth: Causes, clinical characteristics and outcome - Milica Šipovac; Jelena Galović; Ljubica Pavlović-Trifunović; Mirjana Perin; Bojan Petrović (Биомедицинска истраживања, 2018)
Introduction: Tooth injuries are very common in children. They occur during intense physical and mental development, which complicates the clinical presentation, diagnosis, therapy and prognosis of the injured teeth. Tooth intrusion (Intrusion dentis) is an injury to the surrounding tissue characterized by axial tooth movement towards the jawbone tissue followed by serious damage to the periodontium. The aim of the paper is to determine the etiological factors, clinical presentation and outcomes of tooth intrusion with the aim of making prognosis based on the previous data. Methods: The examination was based on the medical records of patients diagnosed with tooth intrusion from 2006 to 2016. It included 17 females and 37 males, aged 1 to 15 years. Using clinical and radiographic data obtained from medical records, 51 decidious and 35 permanent intruded teeth were analyzed. The degree of intrusion was estimated as the following: mild intrusion (less than 3mm), moderate intrusion (3-7 mm) and severe intrusion (greater than 7 mm). The medical records held data on complications and the outcome of tooth intrusion. Results: In most cases, tooth intrusion occurred as a result of falling while running (45.59%). In addition to tooth intrusion, the injuries of dental hard tissue, the soft tissue of lip, cavity and maxilla, and, where the injuries to the adjacent teeth were concerned, crown fracture (15%), avulsion (13%) and luxation (13%) were diagnosed. There was a statistically significant difference in the time passed until complete re-eruption of both decidious (p = 0.007) and permanent (p = 0.001) teeth occurred. The most favorable outcome was evaluated in mildly intruded teeth. Complications occurred irrespective of the degree of intrusion. Conclusion: Spontaneous re-eruption without complications usually occurs in mildly intruded teeth. Complications arise as a result of mechanical trauma.
Keywords: tooth intrusion; mixed dentition; dental trauma